Kontribusi Sekolah Dalam Meningkatkan Kinerja Guru Dalam Proses Pembelajaran Daring Di SMP Muhammadiyah 4 Medan - Nusa, Juhari; Zailani, Zailani (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The obstacles faced by teachers regarding media indicators are that some teachers still need time to learn and understand in advance about online digital applications (google class, google meet, and zoom), because some teachers are still not skilled in operating these online digital applications and teachers are still familiar with the use of whatsapp groups in delivering material and giving assignments to students. The biggest inhibiting factor is the lack of an internet network so that there are often obstacles in the learning delivered by the teacher so that many students do not understand the material presented so that they are bored and bored in this online learning. So that the learning outcomes obtained online are decreasing. Based on the place where the learning activities are carried out, the learning facilities can be grouped into two, namely: (1) learning facilities at school and (2) learning facilities at home. Learning facilities in schools such as learning tools, teaching aids, learning media, school buildings, libraries, school offices. The learning facilities at home are learning aids and learning equipment and supplies. In general, the efforts made by SMP Muhammadiyah 4 Medan in fostering and improving teacher competence and performance include: Sending teachers to attend training, upgrading, workshops, and seminars. Completing the facilities and various media to support learning activities. Comparative study activities carried out by schools are with a group of interests to visit or meet certain objects that have been prepared and take place in a relatively short time. Provide exemplary, encouragement, motivation and inspire the conscience of teachers to be aware of their duties and responsibilities as teachers.